2011
DOI: 10.1111/j.1420-9101.2011.02353.x
|View full text |Cite
|
Sign up to set email alerts
|

Eumelanin- and pheomelanin-based colour advertise resistance to oxidative stress in opposite ways

Abstract: The control mechanisms and information content of melanin‐based colourations are still debated among evolutionary biologists. Recent hypotheses contend that molecules involved in melanogenesis alter other physiological processes, thereby generating covariation between melanin‐based colouration and other phenotypic attributes. Interestingly, several molecules such as agouti and glutathione that trigger the production of reddish‐brown pheomelanin have an inhibitory effect on the production of black/grey eumelani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 47 publications
1
57
1
3
Order By: Relevance
“…A key aspect in understanding the maintenance of the female‐limited color polymorphism in ischnuran damselflies that has thus far, however, been neglected is the possibility that color morphs could be signaling alternative reproductive strategies (see Roulin, 2004; Roulin & Bize, 2006 and references therein). This idea has recently received considerable support, with increasing evidence suggesting that the pigments necessary to produce alternative colors may have pleiotropic effects on physiological attributes (Armbruster, 2002; Eliason, Shawkey, & Clarke, 2016; Forsman, Ringblom, Civantos, & Ahnesjö, 2002; Merrill, Van Schooten, Scott, & Jiggins, 2011; Roulin, Almasi, Meichtry‐Stier, & Jenni, 2011). Such alternative strategies have only been studied in a handful of male‐polymorphic organisms (Ahnesjo & Forsman, 2003; Hutchings & Myers, 1994; Lank, Smith, Hanotte, Burke, & Cooke, 1995; Tuttle, 2003) and in three female‐polymorphic organisms: butterflies (Ellers & Boggs, 2002), fishes (Craig & Foote, 2001), and recently, reptiles (Galeotti et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A key aspect in understanding the maintenance of the female‐limited color polymorphism in ischnuran damselflies that has thus far, however, been neglected is the possibility that color morphs could be signaling alternative reproductive strategies (see Roulin, 2004; Roulin & Bize, 2006 and references therein). This idea has recently received considerable support, with increasing evidence suggesting that the pigments necessary to produce alternative colors may have pleiotropic effects on physiological attributes (Armbruster, 2002; Eliason, Shawkey, & Clarke, 2016; Forsman, Ringblom, Civantos, & Ahnesjö, 2002; Merrill, Van Schooten, Scott, & Jiggins, 2011; Roulin, Almasi, Meichtry‐Stier, & Jenni, 2011). Such alternative strategies have only been studied in a handful of male‐polymorphic organisms (Ahnesjo & Forsman, 2003; Hutchings & Myers, 1994; Lank, Smith, Hanotte, Burke, & Cooke, 1995; Tuttle, 2003) and in three female‐polymorphic organisms: butterflies (Ellers & Boggs, 2002), fishes (Craig & Foote, 2001), and recently, reptiles (Galeotti et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, recent studies have found a positive correlation between the level of expression of eumelanic traits and some measures of resistance to oxidative stress (e.g., Roulin et al 2011). A key issue remains to better evaluate the possible costs associated with the production and maintenance of such traits, since these costs would ensure honest signaling of individual quality.…”
Section: A-melanocyte Stimulating Hormone and Immune Responsivenessmentioning
confidence: 98%
“…Thus, pheomelanogenesis represents a consumption of glutathione, the main intracellular antioxidant and physiological reservoir of cysteine, while cysteine is not consumed during eumelanogenesis (Ito and Wakamatsu 2008). This has led to the realization that producing eumelanin entails different benefits and costs than producing pheomelanin and that pheomelanogenesis may limit the ability to cope with physiological processes or environmental conditions that generate high levels of oxidative stress (Karell et al 2011;Roulin et al 2011;Galván and Møller 2013;Galván et al 2014). However, the diversity of melanins is more than just eumelanin and pheomelanin.…”
Section: Evolutionary Implications Of Heterogeneity In Melanin Chemistrymentioning
confidence: 99%